Analisis Pengaruh Literasi Keuangan Syariah, Religiusitas, Dan Bauran Pemasaran Terhadap Keputusan Menjadi Nasabah Bank Syariah di Yogyakarta - Ardiyanto, Ardiyanto; Widana, Oka (ITB AAS INDONESIA Surakarta, 2024)
This study examines the influence of Sharia financial literacy, religiosity, and marketing mix strategy on the decision to become a customer of Islamic banks in Yogyakarta. The research employs a descriptive analysis approach and collects data using questionnaires. A sample of 100 randomly selected Yogyakarta residents was analyzed. Structural Equation Modeling (SEM) with SmartPLS 4.0 software was used to test the hypotheses. The results indicate that: (1) Sharia financial literacy does not positively influence the decision to become an Islamic bank customer. (2) Religiosity positively influences the decision to become an Islamic bank customer. (3) The marketing mix strategy positively influences the decision to become an Islamic bank customer. These findings provide valuable insights for Islamic banking institutions to refine their strategies and attract more customers.